Identities and re-meanings of union subject. Ten strain’s nucle i of trade unionism in Chile (Andamios, Revista de Investigación Social, 2016)
The problem of supporting a sustainable cooperation model in the Chilean trade unionism, make us question by a number of phenomena that shape the constitution of subjectivities and identities within the union movement. In the following article we analyze a series of tension knots that cross the constitution of unionism, and perspectives that converge in his bosom. This article focuses on the Action Research methodology for union reactivation.
Keywords: Unions; labor relations; identity; union reactivation